Ethnographic and cultural content in bilingual education - Ballón Aguirre, Enrique (1987)
Two axiomatic statements about the role of languages ​​in national society will make it easier for me to address the reflections announced in the title: the first tells us that languages ​​always play an important role as cohesive culturally organized social groups; they represent, thanks to their respective lexicons and syntaxes, the regulated way in which these groups make themselves intelligible and understand the reality they live in. The second statement, more specific, starts from the fact that the combined historical, anthropological and linguistic study of Peruvian society has configured the following evidence: the multicultural nature of our various manifested social activities agrees with the multilingualism that expresses them.